2019
DOI: 10.6061/clinics/2019/e859
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk in children and adolescents with end stage renal disease

Abstract: OBJECTIVES: To evaluate cardiovascular involvement in children and adolescents with End Stage Renal Disease (ESRD) and to characterize the main risk factors associated with this outcome. METHODS: Cross-sectional study of 69 children and adolescents at renal transplantation and 33 healthy individuals matched by age and gender. The study outcomes were left ventricular mass z-score (LVMZ) and carotid artery intima-media thickness (CIMT). The potential risk factors consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
4
2
0
Order By: Relevance
“…We saw a difference in radial IT and DP MT in the children with pre‐emptive kidney transplants as compared to the KT patients who had preceding dialysis. This is an interesting finding and in line with earlier studies where time in dialysis has been associated with more pronounced cardiovascular impact 30 . However, no significant difference in 8 years survival between pre‐emptive KT and KT after 1–2 years of dialysis was seen in 2091 patients who started RRT before 18 years of age during the time period 1988–2007 9 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We saw a difference in radial IT and DP MT in the children with pre‐emptive kidney transplants as compared to the KT patients who had preceding dialysis. This is an interesting finding and in line with earlier studies where time in dialysis has been associated with more pronounced cardiovascular impact 30 . However, no significant difference in 8 years survival between pre‐emptive KT and KT after 1–2 years of dialysis was seen in 2091 patients who started RRT before 18 years of age during the time period 1988–2007 9 .…”
Section: Discussionsupporting
confidence: 88%
“…11 Compared to healthy controls, Carotid IT was significantly higher among the children with KT and a tendency towards increased cIMT and IT/diameter ratio was also found. Overweight and waist/height ratio are known predictors for increased cIMT in children with KT, 30 in line with higher BMI z-score and waist circumference among the children with KT in our study. Dangardt et al showed an increase in DP IT correlated to increased BMI over 1 year after transplantation, and children with CKD had an increased carotid IT and MT as compared to children with KT.…”
Section: Uhfussupporting
confidence: 89%
See 1 more Smart Citation
“…A potential confounding variable within the methodology of Sinha et al ’s study and an area of future research to be pursued is the effect of anemia due to CKD on LVH, especially in pediatric patients with late-stage CKD. In a cross-sectional study of 69 children with CKD conducted in Brazil, the investigators observed a relationship between LVM and hemoglobin levels, supporting previous literature that LVMI is associated with anemia ( 10 ). CKD impacts cardiovascular outcomes in a variety of ways, including hemodynamic (anemia, arteriovenous fistula, and fluid overload), metabolic (free radical damage), hyperhomocysteinemia, inflammation, and proteinuria, highlighting the complex ways LVH can be affected in the body ( 10 ).…”
Section: The Effect Of Anemia On Lvh As a Potential Confoundsupporting
confidence: 80%
“…A systematic review conducted by Taddei et al also discussed the importance of adult hypertension management in controlling adverse cardiac outcomes, as both BP and fluid overload contribute to LVH in CKD patients ( 9 ). Do Val et al also emphasizes hypertension’s role in unfavorable cardiovascular outcomes in children with CKD and the importance of strict control of SBP in these situations, and the comparative outcomes of these studies are summarized within Table 1 ( 10 ). Sinha et al ’s study shows the relationship between hypertension and cardiac remodeling and reflects the continuing theme in CKD research connecting BP targets to left ventricular outcomes, providing evidence and treatment guidelines to better support pediatric CKD patients.…”
Section: Bp Management At the 50 Th Percentile Is ...mentioning
confidence: 99%